Temperature Distribution in Bio Stove using Saw Dust: An Integrated Project-based Learning - W. Wagiran; M. Mujiyono; Bayu Rahmat Setiadi; Yulianto Eko Wibowo; Fredy Surahmanto; Dendy Aqila Agata; Chinnathan Areeprasert (Indonesian Journal of Science and Technology, 2023)
This paper aims at developing the potential of cellulose-based energy generation using pyrolysis, gasification, and combustion methods with biodegradable waste media. The cellulose-based material used in this study was sawdust. The sawdust was heated using a biomass stove, which was then analyzed in terms of heat conduction and propagation as well as temperature distribution. To ensure the effectiveness of sawdust as the main material in the biomass stove, sawdust particles were pressed and compacted under various pressure conditions. This experiment was integrated with the Project-Based Learning method through the following steps: (1) determination of projects testing, (2) project design, (3) project implementation schedules, (4) project completion and progress monitoring, (5) reports and presentations of project results, and (6) project evaluation. The results provide new findings that the denser sawdust particles correlate with the greater temperature and propagation rate. This can be obtained from the measured temperature distribution. Areas close to the heat source tend to have the same heat propagation. The density of the sawdust particle is the main key point for producing better pyrolysis and gasification process, in which it correlates with long combustion energy. Integrasi This finding opens a new concept and can be used as a reference for other researchers who develop research related to renewable energy from waste, especially when using a biomass stove.  This study also gives ideas for the need for developing project-based learning using the burning of sawdust using biomass stove as a tool for the teaching and learning process.